Young Research Forum Research Papers for Future Megacities on Governance, Water, Planning, and Mobility - Annegarn, Harold J.; Born, Lukas; Bubeck, Steffen; Eltrop, Ludger; Fiechtner, Manuel; Fricke, Katharina; Kasperek, Irmgard; Kimmich, Christian; Kober, Ralf; Kochendörfer, Bernd; Kopec, Jakob; Kozempel, Karsten; et al. (JOVIS Verlag GmbH, 2014)
In addition to senior scientists, who have summarised their main results in the five volumes of the Future Megacities Book Series, ambitious young researchers have also contributed substantially to the German research programme on sustainable development of future megacities. The authors included in this volume were awarded the research programme's Young Researcher's Award in 2013, and a small but exemplary selection of their scientific work is presented here. Main topics are mobility with transit-oriented development and public transport in China, water demand and supply issues in the arid cities of Lima and Urumqi, governance questions in South Africa and India in the wide framework of energy, and improvement of urban planning procedures in Ho Chi Minh City
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Mrz 2021)
Keywords: ARCHITECTURE / General; City planning -- Environmental aspects; Metropolitan areas -- Environmental aspects; Sustainable urban development; Umweltverschmutzung; Verkehrssystem; Internationaler Vergleich; Wasserversorgung; Megastadt; Governance; Stadtentwicklung; Stadtplanung; Verstädterung; Bevölkerungswachstum; Stadt; Anthropogener Einfluss; Bevölkerungsdichte; Aufsatzsammlung